Unique sandwich structure of the pyrazinamide–methylmalonic acid cocrystal: ternary phase diagrams, characterization and property evaluation. Issue 14 (18th March 2022) - Zhang, Jinyan; Liang, Zhihan; Yang, Fei; Ji, Shaochang; Lan, Ping; Liao, Yexin
Abstract : The dissolution process of the PZA–MMA cocrystal. Abstract : A pyrazinamide (PZA)–methylmalonic acid (MMA) cocrystal was prepared and characterized by powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetric analysis (TGA). Hirshfeld surface and energy framework analysis demonstrated that the hydrogen bonds N(1)–H(1A)⋯O(4), O(5)–H(5A)⋯O(1) and O(3)–H(3A)⋯N(3) comprised the most important connections between PZA and MMA in the cocrystal. Ternary phase diagrams of PZA/MMA/acetonitrile or 1-pentanol were constructed at 30/60 °C, and the result revealed that PZA–MMA dissolved incongruently in the selected solvents. Further solubility data regression of PZA–MMA indicated that higher temperature was conducive to 1 : 1 PZA–MMA cocrystal preparation. Moreover, the properties of PZA–MMA were evaluated by the stability test and dissolution study, and the result showed that both the dissolution property and hygroscopicity of the crystals were significantly higher than those of the pure material, which can be ascribed to the special sandwich structure of the cocrystal and the properties of the conformer (MMA).